Moderasi Beragama dalam Praktik Bobahasaan Mongondow (Teks dan Makna Kearifan Lokal Berbagai Sikap Kebahasaan dan Lirik Lagu) - Abd. Karim; Nensia; AM Saifullah Aldeia; St. Aflahah; Abu Muslim (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2021)
This study employed descriptive qualitative method with semiotic approach. This study aimed to reveal the aspect of religious moderation in the language wisdom (Bobahasaan) of Bolaang Mongondow community in Kotamobagu whose language characteristics are suave and subtle, associated with the language style of Malay people which is unique, communicative, and friendly. This study found that the structure and nature of language derived from the local characteristics of Bolaang Mongondow which is very distinctive by its deep meaning, as well as the strength of the utterances influence, shown that this “Bobahasaan” can be an effective mediation tool for every problem in society, including religious issue. Furthermore, if meaning representation and adaptation of the diversity situation in the “Bobahasaan” are conducted, then it will become very potential as a major element in strengthening religious moderation. The tendency to always respect, care for one another and listen to each other in this “Bobahasaan” system was also an important key in maintaining the balance principle and religious moderation. Another aspect was the great wisdoms in this area namely pogugutat. Which caused the normative identification of moderation values can be easily extracted. The implication of this research was the acquisition of data and information on language wisdom which was meaningful in the local wisdom of the community can be used as an important instrument in the development of religious moderation. Keywords: Bobahasaan, local wisdom, religious moderation, orang Mongondow Penelitian ini mengoperasionalkan metode kualitatif deskriptif dengan pendekatan semiotik. Penelitian ini bertujuan untuk mengungkap aspek moderasi beragama dalam kearifan berbahasa (Bobahasaan) masyarakat suku Bolaang Mongondow di Kotamobagu, yang memiliki karakteristik Bahasa yang sangat lembut dan halus, dikaitkan dengan corak berbahasa orang melayu Manado dengan aksennya yang sangat khas, komunikatif, dan bikin akrab. Penelitian ini menemukan bahwa struktur dan pembawaan Bahasa yang berasal dari karakteristik lokal Bolaang Mongondow yang sangat khas dengan ketinggian maknanya, serta kekuatan pengaruh penuturannya. Hal itu menunjukkan bahwa Bobahasaan ini bisa menjadi alat mediasi efektif untuk setiap persoalan di masyarakat, termasuk di dalamnya persoalan keberagamaan. Lebih lanjut, jika dilakukan representasi makna dan adaptasi situasi keberagamaan dalam Bobahasaan itu, maka sangat potensial menjadi unsur utama penguatan moderasi beragama. Kecenderungan untuk senantiasa menghargai, saling menjaga dan saling mendengarkan dalam sistem Bobahasaan ini juga menjadi kunci penting penjagaan prinsip keseimbangan dan moderat dalam beragama. Aspek lainnya adalah adanya payung kearifan besar di daerah ini berupa pogugutat, menjadikan identifikasi normatif terkait nilai-nilai moderasi dapat dengan mudah digali. Implikasi penelitian ini adalah diperolehnya data dan informasi kearifan bahasa yang sarat makna dalam kandungan kearifan lokal masyarakat yang dapat dijadikan instrument penting dalam pengembangan moderasi beragama. Kata Kunci: Bobahasaan, kearifan lokal, moderasi beragama, torang Mongondow